1994
DOI: 10.1200/jco.1994.12.10.2176
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy followed by autologous peripheral-blood stem-cell transplantation for patients with Hodgkin's disease and non-Hodgkin's lymphoma using unprimed and granulocyte colony-stimulating factor-mobilized peripheral-blood stem cells.

Abstract: The use of G-CSF-mobilized PBSC after high-dose myeloablative therapy resulted in a rapid, complete, and sustained hematopoietic recovery. Disease-free survival over 2 years can be achieved in some patients with relapsed lymphoma after high-dose therapy and PBSC transplantation. However, longer follow-up is required to confirm the curability of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 41 publications
1
72
0
Order By: Relevance
“…Peripheral blood stem cell (PBSC) transplantation is now used extensively to provide rapid and durable hematopoietic reconstitution after high-dose chemotherapy for malignant disease [1,2]. Mobilization techniques include the administration of hematopoietic growth factor after chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood stem cell (PBSC) transplantation is now used extensively to provide rapid and durable hematopoietic reconstitution after high-dose chemotherapy for malignant disease [1,2]. Mobilization techniques include the administration of hematopoietic growth factor after chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when compared with BMT, reinfusion of G-CSF-mobilized PBSCs was found to reduce the number of plt infusions needed (6 vs 10, Po0.001) and the time to plt and neutrophil engraftment (16 days vs 23 days, P ¼ 0.02; 11 days vs 14 days, P ¼ 0.005, respectively). Nademanee et al 84 harvested stem cells in 95 patients with lymphoma after the s.c. or i.v. administration of regimens of G-CSF 10 mg/kg daily for a median of 12 days (range: 4-23; n ¼ 39), G-CSF 5 mg/kg daily for a median of 12 days (range: 8-27; n ¼ 26) or no mobilizing therapy (n ¼ 30).…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…The authors reported median CD34 þ cell yields of 6.2 Â 10 6 cells/kg, 3.4 Â 10 6 cells/kg and 1.2 Â 10 6 cells/kg in the respective treatment groups. 84 Narayanasami et al 28 mobilized stem cells in 22 patients with NHL or HD by using G-CSF 10 mg/kg s.c. daily for 4 days before the start of apheresis and reported a median CD34 þ cell collection of 2.5 Â 10 6 / kg; approximately 50% of these patients required only one apheresis session, whereas 4% of patients required three sessions.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…PBSCs mobilized after chemotherapy, G-CSF and plerixafor resulted in timely engraftment after high-dose chemotherapy. The median day to neutrophil recovery was 11 (range [8][9][10][11][12][13][14][15][16][17][18][19][20]. The median day to plt recovery without transfusion was 13 (range 7-77).…”
Section: Transplantation and Engraftmentmentioning
confidence: 99%